Fragilité des limites conventionnelles à l’arbitrage de grief : l’arrêt Parry Sound - Morin, Me (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
AbstractIn a recent ruling (Parry Sound (District) Social Services Administration Board v. O.P.S.E.U., Local 324, 2003 SCC 42), the Supreme Court of Canada states that an arbitrator has jurisdiction to hear a dispute that involves rights guaranteed by codes, charters and employment legislation even if the arbitrator has been barred from such recourse under a collective agreement. In the case at issue, an employee with probationary status benefited from maternity leave and was discharged upon her return.Despite the clarity of the wording under the collective agreement stating that a probationary employee may not resort to arbitration, a grievance was filed and was worded as follows: [Translation] “. . . was discharged without reason and this decision is arbitrary, discriminatory, unjust and vitiated by bad faith.”Owing to the rights vesting in the employee under the Employment Standards Act (Ontario), the Board of Arbitration ruled on its own jurisdiction to hear such a grievance. This decision was quashed in judicial review (Superior Court) and but was then upheld in Court of Appeal and once again by the Supreme Court of Canada (majority 7/9).The Supreme Court of Canada began by making several observations concerning the criteria of judgment applicable to judicial review, namely that which is considered patently unreasonable. An attempt was made to distinguish between an unreasonable decision and one that would be patently unreasonable. It seems to us that such a distinction remains ambiguous and further confuses the exercising of a fair judicial review; unreasonableness should not be graded by degrees.In a second approach, the ruling establishes the relationship between State standards (Codes, Charters and employment legislation) and contractual standards. Working from the basis that State standards would be incorporated into the collective agreement, the Court establishes that the limit imposed upon the collective agreement regarding access to arbitration had the practical effect of denying the right to maternity leave, elsewhere guaranteed by law. For this reason, the arbitrator had to intervene and exercise control in order to ensure respect for established standards of public order. To achieve these ends, the Supreme Court of Canada seemed to experience considerable difficulty in qualifying the collective agreement and classified it in the category of private contracts. Such a categorization, confined to the traditional “public/private” dichotomy, dismisses the true legal and desired effect seeking to make the collective agreement a regulatory labour provision complementary to statutes governing public order and intimately related to the latter.In support of his line of reasoning, Judge Iacobucci, on behalf of the majority (7/9), repeatedly referred to the ruling: McLeod v. Egan, [1975] 1 S.C.R. 517. The referrals denied under this ruling are hardly convincing and uselessly weigh down the reasoning. Moreover, Judge Major (dissenting) also referred to it and considered that Judge Iacobucci was reading into the McLeod v. Egan ruling a purport that it just does not have.In all, we believe that the codes, charters and employment legislation serve as the basis upon which the collective agreement is built and, consequently, the parties’ contractual freedom both derives from this basis and is limited thereto. This interrelation would be analogous to that of the Constitution and employment statutes, without it being possible to affirm that the Constitution would be found to be a part of each of these statutes.This ruling is especially interesting because it recognizes the employee’s right to resort to arbitration in order to ensure respect for guarantees stipulated in employment legislation, despite wording to the contrary in the collective agreement. Parties to collective agreements and arbitrators must therefore respectively correct their approach and grant access to arbitration for all employees from the very moment that their fundamental rights are jeopardized in any way.